The Influence of Retirement Readiness, Pre-Retirement Training, and Retiree Motivation on Organizational Satisfaction of PWRI Administrators in Bekasi - Sabila Amara Rachma; Endang Iryanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The increase in life expectancy in Indonesia has led to a rising elderly population, including in Bekasi City. This poses a challenge in ensuring sustainable quality of life for the elderly. This study aims to analyze the influence of retirement readiness, retirement training, and retiree motivation on organizational satisfaction among members of the Indonesian Retired Civil Servants Association (PWRI) in Bekasi City. A quantitative approach was used with proportional stratified sampling involving 80 representatives of PWRI managers at city, sub-district, and village levels. Data were analyzed using the Partial Least Square (PLS) method. The findings show that retiree motivation significantly influences organizational satisfaction, while retirement readiness and retirement training do not. Hence, the Bekasi City PWRI and local government should enhance synergy in designing training and empowerment programs tailored to retirees’ interests. Social support should also be reinforced to improve retirees quality of life comprehensively.